Effect of Federal Constitutional Framework to Marine Environmental Law, Policy and Administration in Malaysia - Mokhtar, Khairil Azmin; Mustafa, Maizatun (INSI Publications, 2012)
One of the main obstacles in having effective legislations and in establishing efficient administrative mechanism to implement and enforce marine environmental laws and policies in Malaysia is due to the federal system of government which divides legislative and executive/administrative power between two levels of government, namely the federal government and the state governments. Environment becomes a contentious subject matter and issue in Malaysia because the division of power in the constitution neither put environment in federal exclusive sphere nor state exclusive sphere. The court’s decision to define environment ‘according to context’ means the subject matters that may constitute environment may come within state government’s jurisdiction, federal government’s jurisdiction or concurrent power of both governments. As a result there is uncertainty of jurisdiction on duties and responsibilities over environmental matter. The complexity regarding jurisdiction over environmental matters is compounded by the fact that the two East Malaysian states have extra power compared to the rest of the states, which makes the determination of environmental matters relating to the two states to a certain extent different compared to other states.